2014
DOI: 10.1155/2014/848632
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Dietary Fatty Acids with Tumour Necrosis Factor Family Cytokines during Colon Inflammation and Cancer

Abstract: Intestinal homeostasis is precisely regulated by a number of endogenous regulatory molecules but significantly influenced by dietary compounds. Malfunction of this system may result in chronic inflammation and cancer. Dietary essential n-3 polyunsaturated fatty acids (PUFAs) and short-chain fatty acid butyrate produced from fibre display anti-inflammatory and anticancer activities. Both compounds were shown to modulate the production and activities of TNF family cytokines. Cytokines from the TNF family (TNF-α,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 187 publications
(206 reference statements)
0
47
0
5
Order By: Relevance
“…The relationship between inflammation and cancer promotion and progression has already been postulated [40], with evidences of the involvement of several pro-inflammatory cytokines [like tumor necrosis factor (TNF), interleukins (IL), chemokines], inflammation-inducing enzymes [like cyclooxygenase-2 (COX-2) and matrix metalloproteinase-9 (MMP-9)], adhesion molecules, and transcription factor activation [such as nuclear factor κB (NF-κB) and hypoxiainducing factor 1α (HIF-1α)] that results in inflammatory gene products [16,23]. These gene products, essentially controlled by NF-κB, are strictly linked with the carcinogenic process, since they are related with tumor cell survival, antiapoptotic signaling pathways, proliferation, invasion, and angiogenesis [16].…”
Section: Butyrate and Colon Cancer Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between inflammation and cancer promotion and progression has already been postulated [40], with evidences of the involvement of several pro-inflammatory cytokines [like tumor necrosis factor (TNF), interleukins (IL), chemokines], inflammation-inducing enzymes [like cyclooxygenase-2 (COX-2) and matrix metalloproteinase-9 (MMP-9)], adhesion molecules, and transcription factor activation [such as nuclear factor κB (NF-κB) and hypoxiainducing factor 1α (HIF-1α)] that results in inflammatory gene products [16,23]. These gene products, essentially controlled by NF-κB, are strictly linked with the carcinogenic process, since they are related with tumor cell survival, antiapoptotic signaling pathways, proliferation, invasion, and angiogenesis [16].…”
Section: Butyrate and Colon Cancer Preventionmentioning
confidence: 99%
“…Chronic intestinal inflammation that characterizes patients with inflammatory bowel disease (IBD), namely Crohn's disease and ulcerative colitis, may be related with colorectal cancer pathogenesis [40]. Butyrate-producing bacteria as well as butyrate concentration in fecal samples were found decreased in patients with ulcerative colitis in comparison with healthy individuals.…”
Section: Butyrate and Colon Cancer Preventionmentioning
confidence: 99%
“…The possible interaction between dietary FA and DF intakes has been previously shown in a population-based case-control study (17). Also, recently, an interaction has been reported of dietary n-3 PUFA and shortchain FA intakes produced from fiber with cytokines during colon inflammation and cancer (55). In addition, the studies reporting a positive association between n-3 PUFA intake and advanced CRC or CRC included subjects with low consumption of DF intake (median: 10-14 g/d; mean: 17-19 g/d) (36,39), whereas the studies reporting no association between n-3 PUFA intake and CRC included subjects with a higher median DF intake (16-23 g/d) (40).…”
Section: Discussionmentioning
confidence: 71%
“…Alteration of oncogenes or tumor-suppressor activity often occurs at the critical points of the development of colon cancer (4). For example, cytokines from the TNF family have potent inflammatory activities and play an important role in cancer development by regulating apoptosis in colon cancer (5). Chen et al reported that the tumor suppressor p53 promotes mitochondrial DNA base excision to regulate the development of colon cancer (6).…”
Section: Introductionmentioning
confidence: 99%